Personality styles and coping strategies : the relationships between sociotropy/autonomy, coping, and mood : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Parkhill, Gillian Mary (Massey University, 2000)
Beck's (1983) personality-event congruence hypothesis proposes that individuals high in the personality constructs of sociotropy and autonomy are vulnerable to the development of depression when facing stressful life events that are congruent with their personality dimension. The present study investigated if the stronger empirical support for Beck's hypothesis for sociotropy, than for autonomy, is due to differences in coping strategies used by sociotropic and autonomous people. Using a cross-sectional retrospective research design, with a non-clinical student sample, the present study tested the hypotheses that people with different levels of sociotropy/autonomy use different coping strategies, and that coping mediates the relationship between sociotropy/autonomy and mood in the face of stressful events. The roles of gender and social support in that relationship were also explored. While sociotropy/autonomy levels did not affect coping patterns found between interpersonal and achievement events, sociotropy/autonomy was found to influence coping in general. Participants with low levels of sociotropy and autonomy showed decreased use of self-control, accepting responsibility, and escape-avoidance coping. The coping strategies of self-control and escape-avoidance mediated the relationship between sociotropy/autonomy and positive affect, while escape-avoidance mediated the relationship between sociotropy/autonomy and negative affect. Women had higher sociotropy scores than men, and although participants low in both sociotropy and autonomy reported higher levels of social support, no gender differences in social support were found. Social support had a positive influence on positive affect and a negative influence on negative affect. Men used more planful problem-solving than women, but the gender differences in coping were unrelated to coping differences found between the different sociotropy and autonomy levels. These findings are discussed within the framework of the personality-event congruence hypothesis.
Keywords: Stress (Psychology); Adjustment (Psychology); Personality; Coping; Coping strategies